Metallogenic map of Peru: operations and mining projects - Instituto Geológico Minero y Metalúrgico. Dirección de Recursos Minerales y Energéticos (2025)
[ENG] --- The Metallogenic Map of Peru at a scale of 1:1,000,000 (De Las Casas & Ponzoni, 1969), sponsored by the National Mining and Petroleum Society, has served as a foundation for subsequent metallogenic studies. Updated versions were developed by Bellido, E. (1972), Ponzoni, P. (1980), and Canchaya & Aranda (2001). In 2001, as part of the Andean Multinational Project, a metallogenic map of the border region between Argentina, Bolivia, Chile, and Peru, also at a 1:1,000,000 scale, was produced (Zappettini et al., 2001). Subsequently, Cardozo (2002) introduced a map delineating mineralized belts based on deposit types. In 2007 and 2008, Quispe et al. created a new metallogenetic map that identified 23 metallogenetic belts, integrating geotectonic domains, regional fault systems, and a classification of ore deposits based on mining operations and projects.